2019
DOI: 10.1371/journal.pone.0211038
|View full text |Cite
|
Sign up to set email alerts
|

PopRank: Ranking pages’ impact and users’ engagement on Facebook

Abstract: The advent of social networks revolutionized the way people access to information sources. Understanding the complex relationship between these sources and users is crucial. We introduce an algorithm, that we call PopRank, to assess both the Impact of Facebook pages as well as users’ Engagement on the basis of their mutual interactions. The ideas behind the PopRank are that i) high impact pages attract many users with a low engagement, which means that they receive comments from users that rarely comment, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Country competitiveness Field complexity [196] Social User-page engagement in Facebook User engagement Page impact [197] Ecological Plant-pollinator Pollinator importance Plant vulnerability [71] Table 5: Applications of the fitness-complexity algorithm and its variants to diverse systems. For each system, we provide a brief interpretation of both Fitness and Complexity score, and we refer to the mentioned references for all the details.…”
Section: Countryresearch Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Country competitiveness Field complexity [196] Social User-page engagement in Facebook User engagement Page impact [197] Ecological Plant-pollinator Pollinator importance Plant vulnerability [71] Table 5: Applications of the fitness-complexity algorithm and its variants to diverse systems. For each system, we provide a brief interpretation of both Fitness and Complexity score, and we refer to the mentioned references for all the details.…”
Section: Countryresearch Fieldmentioning
confidence: 99%
“…At the same time, the rankings obtained with γ > 1 tend to be more sensitive to structural perturbations of the network's structure [72], which is a drawback especially for systems where a non-negligible fraction of the links might be unreliable, such as the World Trade [45,198]. A different generalization of the fitness-algorithm was introduced by Zaccaria et al [197] to rank users' engagement and pages' impact in Facebook; they found that the resulting algorithm (which they called PopRank ) can reliably predict the future activity of a Facebook page.…”
Section: Countryresearch Fieldmentioning
confidence: 99%
“…Compared to the Methods of Reflections [6] and the equivalent Economic Complexity Index 5 , the fitness-complexity better quantifies countries' and products' structural importance in the country-product bipartite network [7]; it substantially improves the GDP growth predictability [8]; it identifies correctly high-growth countries such as China and India, which are far from the top-ranked countries by ECI 6 . Because of its effectiveness, the FC algorithm itself has seen modifications [7,9,10] and applications in other domains [11][12][13][14]. Compared to its variants such as the minimal extremal metric [9] and the generalized fitness-complexity algorithm [7], the original fitness-complexity algorithm is substantially more robust with respect to noisy input data, which makes it better suited for the analysis of world trade data [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…When the contents consumed by users pertain to a certain narrative, such as in the case of political news, it has been pointed out selective exposure dominates users' attention patterns [1,2]. We tend to select information adhering to our system of beliefs and to ignore dissenting information [3,4,5,6]. However, other factors may influence content selection, especially if we consider the huge and heterogeneous volume of recreational material present online.…”
Section: Introductionmentioning
confidence: 99%